Functional characterization of a cysteine protease essential for the assembly of the Clostridioides difficile spore surface layers - Olivença, Carmen Maria Antunes (2022)
Clostridioides difficile is a Gram-positive, strict anaerobe, sporeforming organism, and the leading cause of a range of intestinal diseases linked to antibiotic therapy. C. difficile infection begins with the ingestion of spores that are also the vehicle for transmission. Proper assembly of the spore surface layers is important for the resilience of spores, their interaction with host cells and proper germination. Here, we focused on the characterization of YabG, a cysteine protease conserved among spore-formers. YabG processes substrates involved in spore germination and is required for the transcription of a gene, cdeM, which codes for a protein with a key role in the structural organization of the spore surface and required for host colonization. YabG has an N-terminal domain separated by a linker with a hinge region, from a C-terminal catalytic domain with the fold of a response regulator. We showed that unlike other cysteine proteases, YabG does not require removal of the N-terminal domain for activity. Rather, we present data suggesting that this domain is important for substrate engagement. Nevertheless, a catalytic inactive variant is cleaved in trans by the WT enzyme, at one of several arginine residues located in the hinge region. Multiple arginine to alanine substitutions in this region, result in a form of YabG able to process its substrates in vitro and in vivo but that fails to activate cdeM transcription. YabG may function by removing a cdeM repressor. Consistent with this model, we found two direct repeats in the cdeM regulatory region that function in cis to bind a repressor. Accordingly, titrating the repressor bypasses the need for YabG. Given its central role in spore assembly and its unique structural and functional features, YabG is an attractive therapeutical target to interfere with the central role of spores in infection and transmission.